ANALYSIS OF FACTORS AFFECTING ACCOUNTING STUDENTS IN CAREER SELECTION AS PUBLIC AND NON-PUBLIC ACCOUNTANTS - Putra, Adrie (Jurnal Ekonomi : Journal of Economic, 2021)
This study aims to find out the factors that influence the career selection of accounting students of Esa Unggul University. In the study the factors measured using financial award variables, professional training, professional recognition, social values, work environment, market considerations and personalities had an influence on the career selection of accounting students as public accountants and non-public accountants.The data collection method in this study was obtained by distributing questionnaires to accounting students of Esa Unggul University and taking samples of 100 respondents.The results of the analysis showed that the variables of financial awards, professional training, professional recognition, social values, work environment, market considerations and personalities had a significant influence on career selection as a public accountant or non-public accountant.This study aims to determine the factors that affect the career choice of Esa Unggul University accounting student. In the study factors were measured using a variable financial reward, professional training, professional recognition, social value, work environment, market considerations and personality has an influence on the selection of the accounting student career as a public accountant or non-public accountant.Methods of data collection in this study were obtained using by distributing questionnaires to Esa Unggul University accounting student and take the sample of 100 respondents.Results of the analysis showed financial variable awards, professional training, professional recognition, social values, work environment, market considerations and personality has a significant influence on the selection of a career as a public accountant or non-public accountant. Keywords: financial awards, professional training, professional recognition, social values, work environment, market considerations and personality.